Seismic reinforcement of a linac installation. Issue 4 (8th March 2021) - Szegedi, Martin; Sarkar, Vikren; Paxton, Adam; Rassiah, Prema; Salter, Bill J.
Abstract: The local building requirements to secure medical equipment in seismically active areas in the United States are based on recommendations of the American Society of Civil Engineers. In our institution we have recently acquired new linear accelerators, one of which had to be installed in an existing vault and one in a new vault. Since we are in a seismic active area, changes in the local code required us to start placing the new linacs seismically stable. Here, we describe the necessary steps taken to ensure a seismically sound installation of our linacs. For the linac installation to be seismically stable, the linac base frame has to be seismically fixed into the vault floor. The installation of a new linac into an existing vault requires verification of a structurally sound base frame. Knowledge of the previously applied fixation of such is needed and exploratory removal of grouted floor helped in the verification. Understanding the additional load requirements for the locality allows to account for the existing fixation and can potentially reduce the work needed to achieve seismic fixation requirements. For a prospective seismic installation the new linac base frame can be directly installed with the necessary strength. In addition the actual workflow is straight forward and vendor recommendations can be used. In both cases the vendor provided seismic calculations serve as baseline from which a facility should be work from. It is the facilities task to verify the correct installation of a linac in their specific location. An understanding of the seismic landscape can facilitate an appropriate installation at minimal additional cost.